2015
DOI: 10.1002/2015jc010793
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional streaming in the seabed boundary layer beneath propagating waves with an angle of attack on the current

Abstract: The effect of three‐dimensional wave‐induced streaming on the seabed boundary layer is investigated for following and opposing waves and current where the wave propagation forms a nonzero angle with the current. It is shown that the seabed boundary layer flow results from an interaction between the classical wave‐current interaction (reducing the mean velocity relative to current alone), Longuet‐Higgins streaming (forcing the flow in the wave propagation direction), and streaming caused by turbulence asymmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…An equivalent wave has been applied to represent the random waves using the rms (root-mean-square) value of the measured velocity amplitude. The present model has earlier been successfully applied on seabed boundary layers (regular and random waves plus current) by Holmedal et al (2003) and on sediment transport (Holmedal et al 2004;Holmedal and Myrhaug 2006;Holmedal and Myrhaug 2009;Holmedal et al 2013;Afzal et al 2015); a convincing agreement between measurements and predictions of turbulent flow quantities and sediment concentration was obtained. The governing equations for conservation of momentum and mass are given as:…”
Section: Model Formulationsupporting
confidence: 60%
“…An equivalent wave has been applied to represent the random waves using the rms (root-mean-square) value of the measured velocity amplitude. The present model has earlier been successfully applied on seabed boundary layers (regular and random waves plus current) by Holmedal et al (2003) and on sediment transport (Holmedal et al 2004;Holmedal and Myrhaug 2006;Holmedal and Myrhaug 2009;Holmedal et al 2013;Afzal et al 2015); a convincing agreement between measurements and predictions of turbulent flow quantities and sediment concentration was obtained. The governing equations for conservation of momentum and mass are given as:…”
Section: Model Formulationsupporting
confidence: 60%
“…They studied the interaction between the classical wave-current interaction mechanism and the two streaming mechanisms, also affecting the direction and veering of the resulting current, which cannot be measured neither in closed channels nor in large wave flumes. Overall, Afzal et al (2015b) yields new insight into wave-current seabed boundary layer flow characteristics.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies such as Holmedal & Myrhaug (2009) have focused on sediment transport due to the Longuet-Higgins streaming mechanism under waves alone, while Holmedal et al (2013) have focused on following and opposing waves and current. Recently, Afzal et al (2015b) investigated the effect of streaming on the wave-current sea bed boundary layer for waves with an angle of attack on the current using numerical simulations. They studied the interaction between the classical wave-current interaction mechanism and the two streaming mechanisms, also affecting the direction and veering of the resulting current, which cannot be measured neither in closed channels nor in large wave flumes.…”
Section: Introductionmentioning
confidence: 99%
“…[] and Afzal et al . [], among others, numerically showed that the effects of both progressive and turbulent asymmetry streamings on wave‐current interactions can be very significant.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan and Madsen [2015] (YM15 hereafter) reported experiments of currents in the presence of asymmetry oscillatory flows and showed that the turbulence asymmetry streaming has a pronounced effect on currents, which can even invalidate the basic wave-current interaction proposed by the GM model. Holmedal et al [2013] and Afzal et al [2015], among others, numerically showed that the effects of both progressive and turbulent asymmetry streamings on wave-current interactions can be very significant.…”
Section: Introductionmentioning
confidence: 99%